2005
DOI: 10.1021/ma051267r
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Morphology of Polyanhydride Copolymers

Abstract: The microphase separation in polyanhydride random copolymers composed of 1,6-bis(pcarboxyphenoxy)hexane and sebacic acid is described. Though the copolymers are random, the monomers are sufficiently long and the segment-segment interaction parameter is sufficiently high to promote microphase separation when the copolymer is rich in one component. Solid-state NMR spin diffusion experiments and synchrotron small-angle X-ray scattering are used to discern the length scales of the microphase separation. Both techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Faghihi et al 8 reported that random copolymers of butyl acrylate and methyl methacrylate showed nanophase segregation according to DMA, DSC and 13 C-NMR spin diffusion experiments. Kipper et al 9 reported that random copolymers of 1,6-bis(p-carboxyphenoxy)hexane and sebacic acid undergo microphase separation because of large differences in the segment-segment interaction parameters. In this study, the crude NBRs did not show a phase separation structure.…”
Section: Pulsed 1 H-nmr Analysis Of Crude Nbrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Faghihi et al 8 reported that random copolymers of butyl acrylate and methyl methacrylate showed nanophase segregation according to DMA, DSC and 13 C-NMR spin diffusion experiments. Kipper et al 9 reported that random copolymers of 1,6-bis(p-carboxyphenoxy)hexane and sebacic acid undergo microphase separation because of large differences in the segment-segment interaction parameters. In this study, the crude NBRs did not show a phase separation structure.…”
Section: Pulsed 1 H-nmr Analysis Of Crude Nbrsmentioning
confidence: 99%
“…Although almost all random copolymers show homogeneous morphology, it has been reported that some random copolymers show an inhomogeneous phase structure. 8,9 In the case of NBRs, the existence of phaseseparated structures was suggested by the spin-lattice relaxation time (T 1r ) analysis of CH 2 via the 13 C-NMR inversion recovery method. 10 According to these reports, the inhomogeneity was caused by an intramolecular inhomogeneous structure composed of segments with different monomer sequences and by large differences in the segmental interaction parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For compositions richer in either monomer, the majority component sequence length greatly increased while the minority component remained moderate. Such divergence in number-average sequence length indicates a weak block-like microstructure . Following the same methodology, reactivity ratios were calculated for this library (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Such divergence in numberaverage sequence length indicates a weak block-like microstructure. 25 Following the same methodology, reactivity ratios were calculated for this library (Figure 2b). At compositions between 20:80 and 80:20 CPTEG:SA, the reactivity ratios for both components were near unity.…”
Section: Polymermentioning
confidence: 99%
“…Information from the blend phase behavior, such as the Flory-Huggins parameter and phase transitions, can be used to describe microphase separation in block or weakly segregated random copolymers. 2,3 This microstructure of the polymer may play an important role in the release kinetics of drugs from these polymers. 4 The present study is focused on the miscibility of blends based on the biodegradable polyanhydride homopolymers composed of 1,6-bis(p-carboxyphenoxy)hexane (CPH) and sebacic acid (SA) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%